The Management of Community’s Tourism Learning Resources in Ban Sala-Din, Nakhon Pathom Province - Pantrakool, Saisuda (RMUTI Journal Humanities and Social Sciences, 2021)
The objective of this research was to study the behavior management of community’s tourism learning resources in Ban Sala Din, Nakhon Pathom province. The sample group consisted of 263 villagers in Ban Sala Din community. The research tool was the questionnaires. Data analysis was statistically engaged in frequencies, percentage, means, standard deviation, and content analysis. The research findings were revealed as follows: the most sample group were females who over 50 years old. There were agricultural careers (farming, animals, fisheries). The behavior management of community’s tourism learning resources in Ban Sala Din, Nakhon Pathom province is the averagely high level in the overview and terms of items as follows: the learning resources, the natural resources and culture, the tourism management, the villagers and communities respectively, and the good practice in managing tourism resources, and suggestions from the open-ended question. The villagers gave suggestions that, Local Leaders should be promotion for youth have the participation in tourism management.